STUDY OF LIPASE ACTIVITY DURING DEVEPLOMENT OF CHILO PARTELLUS (SWINHOE) - SAKATE, P.J.; SALUNKIIE, P.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The changes in lipase activity during development of Chilo portellus (Swinhoe) have been studied. Lipase mainly hydrolyses the triglycerides and releases fatty acids. The maximum activity of the enzyme was recorded at optimal pH 7 andtemperature 37 t, 30 min. incubation time, I% enzyme concentration and 5% substrate concentration. During embryogenesis maximum enzyme activity was observed in 5 day eggs. During larval erowth gradual increase in enzyme activity from I to II day, sharp fall from H to 12 day, slow decrease from 12 to 20 day larvae was observed. During metamorphosis maximum enzyme activity was observed in 7 day pupae and decrease from 7-10 day pupae. During adult development maximum enzyme activity was observed in 2- day male and female adults. The physiological role of lipase during development of C. parwIlas is discussed.